A STUDY OF HOCO RESONANCES IN THE OH+CO-]CO2+H REACTION - Hernandez, M; Clary, D (1994)
Quasibound states of the HOCO intermediate in the reaction OH+CO→H+CO2 are studied by means of the stabilization method. A reduced-dimensionality model is used. The calculated resonance positions and lifetimes' agree well with previous quantum scattering calculations. Most of the quasibound states can be assigned approximately to a vibrational excitation in the higher frequency OH vibration and different progressions in the HO-CO stretching mode. Some interesting mode-specific effects in the dynamics of the unimolecular decay are predicted. © 1994 American Institute of Physics.